Refugees and Asylum Seekers In Turkey During The Covid-19 Pandemic - Lalu Jeffrey Alim Wahtum; Sugito Sugito (Syntax Corporation, 2022)
Turkey is one of the most bypassed countries and is occupied by refugees and asylum seekers coming from the Middle East. The problem of refugees in Turkey has become more complicated after the outbreak of the Corona Virus (COVID-19), so that according to the United Nations High Commissioner for Refugees (UNHCR), refugees are the most vulnerable to COVID-19. This study aims to describe how the Turkish government's efforts in providing protection to refugees from the dangers of the spread of COVID-19. This study adapts qualitative methods by utilizing news, journals and books as secondary data. This study found that Turkey has made various efforts by following the guidelines of the World Health Organization (WHO) and also collaborating with UNHCR to protect refugees from COVID-19